The prevalence of learning difficulties among talented, outstanding and ordinary students in Iraq ( A comparative study ) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Based on the researcher's sense of the research problem from two sources, the first of which is her long experience in the educational process, especially the education of the talented, and the second is what the literature of learning difficulties referred to in the talented and who are called (Twice- Exceptional) as some studies concluded that some talented students have some difficulties in different fields, some of which are mental, cognitive, psychological or behavioral, which appear through the frequent boycott of teachers, boredom, withdrawn behavior, etc, moreover, these characteristics are shared by the outstanding students' category, but in more proportions, and the ordinary ones have a greater percentage of the two groups.Some studies and literature indicate that the prevalence of difficulties among talented students is (13%) and there is evidence that this percentage is present among the ordinary and the outstanding, in order to verify this percentage, the aim of the current research is to measure the level of learning difficulties among educational groups, in addition to revealing the realistic percentages of these groups of students and comparing them with the percentage of the criterion (13%) and test the differences between these ratios, to achieve this, the researcher prepared a learning difficulties scale, which consists of (39) items divided into three domains (mental - academic - psychological - emotional). The researcher verified the psychometric properties of the tool and the paragraphs, and it was acceptable, except for three paragraphs that were excluded from the scale due to their lack of sincerity, and thus the total number of paragraphs became (36) paragraphs, the discriminatory validity of the scale was verified and it was able to distinguish between the two extreme groups through the significance of the T-value. The reliability was estimated by the alpha-Cronbach equation and reached (854 and 0) as it is considered acceptable and according to the standard error of the scale (371 and 4). To apply the scale to the main sample, male and female teachers were selected randomly from some talented, outstanding and ordinary schools by five teachers, and they were asked to rate between (5-10) students, after retrieving the answer sheets, it was found that the number of students (350) male and female students was divided into two parts, such as a statistical analysis sample (150) and a main sample (200), the results were as follows:• The arithmetic averages were close between the groups and the mean of the total sample (740 and 68), which is less than the hypothesis mean (72).• The prevalence rates ranged between (12% - 15%).• The differences were significant between the proportions of the groups and in favor of the ordinary• The differences between the arithmetic means were significant and in favor of the ordinary as well.The research concluded that there is a need to pay attention to talented education programs, to focus on selecting experienced teachers, and to apply strategies to address learning difficulties for the groups of students identified in the research. One of the recommendations is that the learning difficulties detection scale should adopt an additional criterion in the detection of talented students.